2017
DOI: 10.1128/jcm.00006-17
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Saramis 4.12 and IVD 3.0 Vitek MS Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry for Identification of Mycobacteria from Solid and Liquid Culture Media

Abstract: During the last decade, many investigators have studied matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for identification of mycobacteria. Diverse and contradictory results indicated that optimal level for routine testing has not been reached yet. This work aimed to assess Vitek MS through two distinct versions, Saramis v4.12 RUO and the IVD v3.0, under conditions close to routine laboratory practice. Overall, 111 mycobacterial isolates were subjected to protein ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
1
32
1
1
Order By: Relevance
“…Alternatively, the Vitek MS IVD system (bioMérieux) uses an identification algorithm method based on a process called "mass binning" that has shown better performance for microorganisms identification than Saramis's method of matching mass signals (13,23,24). Thus, although not evaluated here, an upgrade of the IVD database with the major C. neoformans and C. gattii genotypes by the manufacturer could enhance the power of Vitek MS to well discriminate these microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the Vitek MS IVD system (bioMérieux) uses an identification algorithm method based on a process called "mass binning" that has shown better performance for microorganisms identification than Saramis's method of matching mass signals (13,23,24). Thus, although not evaluated here, an upgrade of the IVD database with the major C. neoformans and C. gattii genotypes by the manufacturer could enhance the power of Vitek MS to well discriminate these microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that reliable identification to species can be done using mycobacteria obtained from subculture on solid-phase medium, such as the Lowenstein-Jensen or Middlebrook 7H10 or 7H11 medium [ 31 38 ]. Identification rates using a Biotyper system was 77% [ 39 ] and detection rate increased from 67% to 94% by using the VITEK MS system for isolates grown on liquid media MGIT, using Saramis v4.12 and IVD v3.0 [ 40 ]. However, these studies all used mycobacterial isolates subcultured from either solid or liquid medium.…”
Section: Introductionmentioning
confidence: 99%
“…However, new databases provided better results [18,19,24], especially if the intensity of characteristic peaks could be assessed by a software algorithm [25]. VITEK MS was also evaluated for MAC speciation, but many MAC species were still not differentiated or were misidentified [26,27]. In the score-oriented dendrogram we obtained, the M. intracellulare isolates clustered together, and the M. chimaera isolates also clustered together, but in two different subgroups.…”
Section: Discussionmentioning
confidence: 99%